2021
DOI: 10.3389/fpsyg.2021.608214
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of the Mentalization Scale (MentS) Within a Mixed Psychiatric Sample

Abstract: Introduction: The concept of mentalizing is nowadays widely used in research as well as in clinical practice. Despite its popularity, the development of an economic assessment is still challenging. The Mentalization Scale appears to be a promising measurement with good psychometric properties but lacking convergent validity with the Reflective Functioning Scale.Objective: This study aims to test the construct validity of the Mentalization Scale through correlations with the gold standard, the Reflective Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
(46 reference statements)
1
11
0
Order By: Relevance
“…Acceptable levels of internal consistency were reported, as well as a meaningful factor structure and correlations with expected factors such as gender, level of education, attachment, personality traits, emotional intelligence and empathy. Other studies have also found similar factor structure and levels of internal consistency (Đorđević and Đorđević, 2019;Benoit, 2020;Stanojević et al, 2020;Ahmadian and Ghamarani, 2021;Bhola and Mehrotra, 2021;Jańczak, 2021;Richter et al, 2021). Investigations of construct validity have found correlations with attachment style (Đorđević and Đorđević, 2019;Benoit, 2020;Stanojević et al, 2020;Jańczak, 2021), empathy (Ahmadian and Ghamarani, 2021;Jańczak, 2021), borderline features, emotional intelligence and personality traits (Jańczak, 2021) in the way that is according to previous knowledge about mentalization.…”
Section: Measuring Mentalizationmentioning
confidence: 57%
See 2 more Smart Citations
“…Acceptable levels of internal consistency were reported, as well as a meaningful factor structure and correlations with expected factors such as gender, level of education, attachment, personality traits, emotional intelligence and empathy. Other studies have also found similar factor structure and levels of internal consistency (Đorđević and Đorđević, 2019;Benoit, 2020;Stanojević et al, 2020;Ahmadian and Ghamarani, 2021;Bhola and Mehrotra, 2021;Jańczak, 2021;Richter et al, 2021). Investigations of construct validity have found correlations with attachment style (Đorđević and Đorđević, 2019;Benoit, 2020;Stanojević et al, 2020;Jańczak, 2021), empathy (Ahmadian and Ghamarani, 2021;Jańczak, 2021), borderline features, emotional intelligence and personality traits (Jańczak, 2021) in the way that is according to previous knowledge about mentalization.…”
Section: Measuring Mentalizationmentioning
confidence: 57%
“…Three subscales can be extracted: Self-Related Mentalization (8 items) , Other-Related Mentalization (10 items), and Motivation to Mentalize (10 items). Previous studies have reported consistent factor structure and good internal consistency ranging from 0.7 to 0.86 ( Dimitrijević et al, 2018 ; Đorđević and Đorđević, 2019 ; Benoit, 2020 ; Stanojević et al, 2020 ; Bhola and Mehrotra, 2021 ; Jańczak, 2021 ; Richter et al, 2021 ). MentS was translated to Norwegian for the present study by two psychologists fluent in English.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Impairment in other-mentalizing can be detected by the ToM tasks with observable reality, which is within the scope of this systematic review. In contrast, the self-mentalizing employed in RF is more responsive to the narrative-based ToM assessments [ 78 , 79 ]. However, sharing the same mentalizing network, other- and self-mentalizing are interactive, providing reciprocal references for each other and contributing to RF.…”
Section: Discussionmentioning
confidence: 99%
“…A sample item is “ Often I cannot explain , even to myself , why I did something ”. The MentS is a relatively new inventory whose consistency, reliability, and validity has been reported to be adequate to good [ 65 , 66 ].…”
Section: Methodsmentioning
confidence: 99%